Electrochemical Behaviour of Copper Nitroprusside Generated in situ Onto the Graphite Paste Electrode Surface, and its Application in the Determination of N-Acethylcysteine - Carmo,D. Ribeiro do (2005)
Copper nitroprusside (CuNP) was generated on the graphite paste electrode using a new methodology of the preparation. The electrochemical studies were carried out by cyclic voltammetry technique. The cyclic voltammogram of the modified electrode, CuNP showed two redox couples (E0)1=0.22 and (E0)2=0.88 V vs. SCE attributed to Cu(I)/Cu(II) and Fe(II)(CN)5NO/Fe(III)(CN)5NO, respectively. The nature of the cation affect the (E0)1 and (E0)2, as current intensity, shifting the E0 for more positive potentials, for two redox processes. The voltammograms obtained with different KCl concentrations (0.1-3.0 mol L-1) exhibit a shift in the (E0)1 to more positive potentials; this change was linear with the supporting electrolyte concentrations change. It was verified that the (E0)1 remained practically constant at pH between 6 and 3. However, a new process with (E0)3 (0.48 V) appears at pH<3 and it was ascribed to formation of intermediary species. The redox couple at (E0)2=0.88 V presents an electrocatalytic response for N-acethylcysteine. The modified graphite paste electrode gives a linear response between 5.0´10-4 to 1.0´10-2 mol L-1 of N-acethylcysteine with a detection limit of 4.5´10-4 (±5%) mol L-1 (n=3) and an amperometric sensitivity of 4.9 mA/mmol L-1. The electrocatalytic oxidation of N-acethylcysteine compounds by the mediator has been used for the determination of N-acethylcysteine in a commercially pharmaceutical available product.